Long-term effects of systematic smoking cessation counselling during acute coronary syndrome, a multicentre before-after study (Swiss Medical Weekly, 2022)
TRIAL DESIGN: In the Special Program University Medicine-Acute Coronary Syndromes (SPUM-ACS) observational study (clinical trial registration: NCT01000701), a multicentre before-after clinical trial, we assessed 5-year outcome after acute coronary syndrome, comparing a systematic with an opportunistic smoking cessation counselling phase.METHODS: We studied smokers who were hospitalised for acute coronary syndromes (ACS), and we assessed self-reported smoking cessation, incidence of cardiovascular events and mortality 5 years after hospital discharge. In the observational phase, from August 2009 to October 2010, only smokers who requested smoking cessation counselling received it during hospitalisation. In the interventional phase, from November 2010 to February 2012, hospitalised smokers with ACS were systematically offered intensive smoking cessation counselling including four telephone calls within 2 months of discharge. Because of the before-after design, the care givers were aware of study phase. The objective was to assess whether systematic counselling to every smoker with ACS has an impact on the long-term smoking cessation rate, incidence of cardiovascular events and mortality. Missing data on smoking cessation were analysed with multiple imputation. The study was not powered to assess differences in 5-year smoking cessation rates or cardiovascular outcomes.RESULTS: Overall, 458 smokers with ACS were included at baseline (225 during the intervention phase and 233 during the observation phase). At 5 years, 286 (62.4%) reported their smoking status (140 for the intervention phase and 146 for the observation phase) and 51 (11.1%) had died. There was no statistically significant difference in the abstinence rate between the interventional phase (75/140, 54%), and the observational phase (68/146, 47%), with a risk ratio with multiple imputation adjusted for age, sex, education and ACS type of 1.13 (95% confidence interval [CI] 0.84–1.51, p = 0.4). The 5-year risk of major acute cardiovascular event was similar in the intervention phase as compared with the observational phase. The multivariate adjusted hazard ratio for all-cause mortality was 0.84 (95% CI 0.45–1.60, p = 0.6). CONCLUSIONS: In this controlled long-term interventional study, systematic intensive smoking cessation counselling in all hospitalised smokers with ACS did not increase 5-year smoking cessation rates, nor decrease cardiovascular event recurrence, as compared with opportunistic smoking cessation counselling during hospitalization.